A choice-based model to reduce primary care load on tertiary hospitals. Issue 3 (2nd July 2020) - Kumar, Kaushal; Bardhan, Amit Kumar
ABSTRACT: In developing countries like India, patients bypass primary health centers (PHCs) and visit larger hospitals for minor ailments and thereby overburden the facilities responsible for specialized consultative health care. This is an undesirable phenomenon and governments are spending more on primary care and setting up more community and primary health centers. In this article, we propose an integer linear programming model for locating PHCs with the explicit objective of reducing unwanted load on tertiary care hospitals. The model offers holistic utilization of existing and new facilities. Moreover, the question of equity in allotment of more desirable facilities which can be built only in limited numbers, is discussed for the first time. This article contributes in the following ways. It describes a decision problem which has social relevance. The dual issues of excessive uneven distribution of health service workload and equity in distribution of public resources in the context of primary care are discussed. Using the novel optimization model developed in the article, major policy directions can be derived. The implementation of this model should ensure better utilization of public money and greater service to the target population. This is also demonstrated through a small real-life case study. A heuristic algorithm has also been proposed for solving the optimization model.